Trends of overweight and obesity among preschool children from 2013 to 2018: a cross-sectional study in Rhine-Neckar County and the City of Heidelberg, Germany - Liu, Weina; He, Mike Z.; Dambach, Peter; Schwertz, Rainer; Chen, Simiao; Yu, Fengyun; Marx, Michael (BMC public health, 2022)
Early childhood overweight and obesity is a growing public health concern worldwide. Few recent studies have addressed how time trends varied by sociodemographic characteristics at the regional level using large and high-quality data. This study determines how time trends vary in the prevalence of early childhood overweight and obesity by age, gender, and migration background at the regional level.